2019
DOI: 10.4143/crt.2017.417
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Oncologic Outcomes between Open and Laparoscopic Radical Nephroureterectomy for the Treatment of Upper Tract Urothelial Carcinoma: A Korean Multicenter Collaborative Study

Abstract: Our findings indicate that LNU provided better oncologic control of IVRFS, CSS, and OS compared with ONU for the management of patients with UTUC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…The impact of chemotherapy for UTUC is still under debate, especially neoadjuvant chemotherapy. Furthermore, some reports showed that receipt of adjuvant chemotherapy was not related to disease progression, death from UTUC, and all-cause death 24 . Management of regional lymph nodes differed among patients because of the retrospective design and absence of a standardized template for lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of chemotherapy for UTUC is still under debate, especially neoadjuvant chemotherapy. Furthermore, some reports showed that receipt of adjuvant chemotherapy was not related to disease progression, death from UTUC, and all-cause death 24 . Management of regional lymph nodes differed among patients because of the retrospective design and absence of a standardized template for lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
“…There is an unusual presentation of high prevalence and female predominance for upper UTUC in the Taiwan and China area . In other Asian areas, such as Japan and Korea, European and American countries, the male:female ratio is from 1.223:2.860 . However, the male:female ratio in Taiwan and China is 0.773:0.838 .…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3] In other Asian areas, such as Japan and Korea, European and American countries, the male:female ratio is from 1.223:2.860. [4][5][6][7] However, the male:female ratio in Taiwan and China is 0.773:0.838. [1][2][3] Several reports attributed this phenomenon to carcinogen exposure, such as arsenic and aristolochic acid.…”
Section: Introductionmentioning
confidence: 99%
“…The institutional review board of each multicenter institution approved this study, including the National Cancer Center (NCC-2016-0040 and 2018-0114-0001) [ 12 ]. The requirement for written informed consent was waived because of the retrospective design of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Based on a previously published paper of the original UCART data set,[ 12 ] the methodology of ONU or LNU and the postoperative follow-up protocols were not standardized but were performed at the surgeon’s discretion. Unless the patient was contraindicated for laparoscopic surgery such as a history of abdominal surgery or high body mass indices, the LNU was indicated as the first surgical choice.…”
Section: Methodsmentioning
confidence: 99%